1985
DOI: 10.1007/bf02386764
|View full text |Cite
|
Sign up to set email alerts
|

Derangement of swallowing in children with myelomeningocele

Abstract: Barium esophagrams performed in 13 children with myelomeningocele demonstrated a variety of swallowing disorders: difficulty in bolus formation, nasopharyngeal reflux, tracheobronchial aspiration. Cricopharyngeal spasm was not identified in this group. Antegrade peristalsis in the distal two-thirds of the esophagus was normal. Gastroesophageal reflux was demonstrated in 8 of the children. Vocal cord paralysis (8/13) and death in early children (7/13) occurred with greater frequency than in the general myelomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…In a prospective study of infants with MMC with flexible fiberoptic laryngoscopy, Linder et al found that 4 out of 22 children had dysphagia with aspiration; 3 of them had bilateral vocal fold motion impairment [Linder and Lindholm, 1997]. Some children will require gastrostomy tube placement to maintain nutrition or prevent pulmonary aspiration [Fernbach and McLone, 1985;Bowman et al, 2001]. Mortality is high in subjects with abnormal respiratory function requiring tracheotomy [McLone and Dias, 2003].…”
Section: Swallowmentioning
confidence: 99%
“…In a prospective study of infants with MMC with flexible fiberoptic laryngoscopy, Linder et al found that 4 out of 22 children had dysphagia with aspiration; 3 of them had bilateral vocal fold motion impairment [Linder and Lindholm, 1997]. Some children will require gastrostomy tube placement to maintain nutrition or prevent pulmonary aspiration [Fernbach and McLone, 1985;Bowman et al, 2001]. Mortality is high in subjects with abnormal respiratory function requiring tracheotomy [McLone and Dias, 2003].…”
Section: Swallowmentioning
confidence: 99%
“…Patients with MMC may present exacerbation of gag reflex due to dysphagia as a result of cranial nerve injury related to the nonclosure of the neural tube . Another explanation for the gag reflex is that people with poor hygiene do not stimulate mouth desensitization, which contributes to the recurrence of reflexes during the dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MMC may present exacerbation of gag reflex due to dysphagia as a result of cranial nerve injury related to the nonclosure of the neural tube. 29 Another explanation for the gag reflex is that people with poor hygiene do not stimulate mouth desensitization, 30 which contributes to the recurrence of reflexes during the dental treatment. In this case, the patient' s reflexes were caused by physical stimuli and handling of the oral cavity, use of saliva ejector, and three-way syringe and even saliva accumulation.…”
Section: Dental Care In Myelomeningocele Patientsmentioning
confidence: 99%
“…Lack of visualization of the rectum on T1‐weighted images raises the possibility of an anatomic abnormality such as distal atresia/obstruction that is often associated with bowel dilation . However, cases of isolated anorectal malformation are not always associated with bowel dilation and therefore may need to be considered along with a functional etiology in fetuses with open spinal dysraphism, who are known to have varying degrees of bowel dysfunction and impaired fetal swallowing . That being said, it has not yet been established what distribution of meconium signal should be expected in the setting of open spinal dysraphism on fetal MRI.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, cases of isolated anorectal malformation are not always associated with bowel dilation and therefore may need to be considered along with a functional etiology in fetuses with open spinal dysraphism, who are known to have varying degrees of bowel dysfunction and impaired fetal swallowing. [13][14][15]…”
Section: Introductionmentioning
confidence: 99%